Digital Confidence Beyond Profit: How Self-Efficacy And Perceived Authenticity Override Risk Preferences In Muslim Generation Z's Sharia Investment Motivation In Surakarta - Aulia Nisrina, Fida; Sukardi, Budi (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
along with growing financial awareness and Islamic values, but their actual participation in the Islamic stock market remains relatively low compared to their demographic potential. This study aims to analyze the influence of self-efficacy, risk preference, and perceived authenticity on Islamic stock investment motivation, with attitude as a mediating variable among Generation Z Muslims in Surakarta City. This study used a quantitative method with an associative approach. Data were obtained from 194 respondents through an online questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that self-efficacy, perceived authenticity, and attitude had a significant positive effect on Islamic stock investment motivation, while risk preference had no significant effect. Attitude was proven to mediate the relationship between self-efficacy and perceived authenticity with Islamic stock investment motivation. These findings confirm that self-confidence and perceived product authenticity are more dominant than risk aversion in shaping investment motivation. The research implications emphasize the importance of increasing self-efficacy and perceptions of authenticity through transparency, halal certification, and digital education to increase Generation Z participation in sharia stock investment.